ANALISIS KUALITAS PELAYANAN MIKROTRANS JAKARTA LINGKAR KOTA ( JAKLINGKO) KOTA JAKARTA - Aprillia, Shinta; Widowati, Nina (Journal of Public Policy and Management Review, 2025)
The analysis of the service quality of Microtrans Jakarta Lingkar Kota (Jaklingko) aims to describe the factors contributing to the service quality of the MikrotransJaklingko transportation mode. This study employs a descriptive qualitative approach through observations and interviews to describe the contributing factors in service quality: functionality, information, convenience, comfort, and safety. Additionally, the analysis focuses on contributing factors such as human resources (HR), systems, operational strategies, and customer interactions. The results indicate that Mikrotrans Jaklingko has positively contributed to the mobility of Jakarta's society. However, there are still shortcomings in certain areas, namely information, convenience, and comfort. Furthermore, systemic factors face several obstacles, such as inconsistent cleanliness of the fleet, driver attitudes that do not support user comfort, and inaccuracies in the information provided through the application. Other challenges include an inefficient payment system, especially during peak hours, and the need for regular evaluations to maintain service quality consistency. A lack of customer satisfaction surveys also hinders understanding of user needs and expectations. This study recommends improvements to a real-time information system, optimization of cashless payment methods, and ongoing training for drivers to enhance professionalism. By addressing these aspects, Mikrotrans Jaklingko can meet the increasingly complex public transportation needs in Jakarta. It is hoped that this research can serve as a reference for developing more efficient, comfortable, and sustainable public transportation services, thereby supporting traffic congestion reduction and improving the quality of life for the residents of Jakarta.